Pengaruh Disiplin Kerja, Motivasi, dan Pengembangan Karir Terhadap Produktivitas Staff BKPSDM di Pemerintah Kabupaten Semarang - Soraya Kamalia; Kiswoyo Kiswoyo (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to find out how the influence of Work Discipline, Motivation, and Career Development on the Productivity of BKPSDM Staff of the Semarang Regency Government. The sample was selected using the census sampling method and a sample of 42 HR staff at the Semarang Regency BKPSDM, data management techniques using SPSS (Statistical Package for the Social Sciences) version 27. The results of the study show that Work Discipline has a significant positive effect on Productivity, Motivation has a significant negative effect on Productivity, and Career Development has a significant negative effect on Productivity.